Dendritic Cells Can Turn CD4+ T Lymphocytes into Vascular Endothelial Growth Factor-Carrying Cells by Intercellular Neuropilin-1 Transfer - Sarah Bourbié-Vaudaine; Nicolas Blanchard; Claire Hivroz; Paul‐Henri Roméo (2006)
Abstract Neuropilin-1 (NRP1) is a transmembrane protein expressed on neuronal and endothelial cells where it plays a crucial role in guiding axons and regulating angiogenesis. We have recently shown that NRP1 also is expressed on dendritic cells (DC) in the human immune system and have proposed a role for NRP1 in the first stages of the immune response. In these studies, we show that NRP1 can be transferred with a high efficiency from human DC to T lymphocytes by trogocytosis. The NRP1 transfer can occur independently of T lymphocyte activation; the amount of NRP1 transferred depends on the NRP1 expression level on APC and is enhanced when T cells are activated through the TCR. Moreover, the NRP1 transfer occurs between specific donor and recipient cells, because no NRP1 transfer is observed between endothelial cells and T lymphocytes or between APCs and CD34+ hemopoietic cells. Finally, we show that a major NRP1 ligand, vascular endothelial growth factor (VEGF)165, is secreted by mature human DCs and binds to NRP1 captured by T lymphocytes. These results show that NRP1 transfer to T lymphocytes during the immune synapse can convert T lymphocytes into VEGF165-carrying cells. Together with the enhanced signaling of VEGF-R2 on endothelial cells in the presence, in trans, of the NRP1–VEGF165 complex, our results suggest that the intercellular transfer of NRP1 might participate in the Ag-independent remodelling of the endothelial vessels in secondary lymphoid organs during inflammation.